TRACE ELEMENT PARTITIONING BETWEEN VAPOR, BRINE AND HALITE UNDER EXTREME PHASE SEPARATION CONDITIONS - Foustoukos D.I.; Seyfried W.E. (My University, 2007)
Experiments were conducted to investigate the partitioning of Li, Br, Rb, Cs and B between vapor, brine and halite during subcritical and supercritical phase separation in the NaCl-H2O system (388-550 °C, 250-350 bars). Results indicate that Li and Br partition preferentially into the low-salinity vapor fluids, while Rb and Cs become more enriched in the coexisting brines. Under more extreme conditions of pressure and temperature in the two-phase region, especially near the vapor-brine-halite boundary, strong salting-out effects imposed on neutral aqueous species enhance significantly partitioning of all trace elements into the low-salinity fluid. Dissolved boron is strongly affected by this and a particularly strong enrichment into vapors is observed, a trend that can be effectively correlated with changes in reduced density. Exclusion of Li, Br, Rb, Cs and B from halite, when precipitated, further increases the solubility of these species in the coexisting Cl-poor fluid. In general, the lack of distortion in the partitioning behavior of trace elements between vapor, brine and/or halite with the transition from subcritical to supercritical conditions in the NaCl-H2O system precludes the need for special reference to the critical point of seawater when interpreting phase relations in submarine hydrothermal systems. The combination of experimentally determined trace element partitioning data with constraints imposed by mineral solubility provides a means to better understand the origin and evolution of hot spring vent fluids. For example, in Brandon hydrothermal system (21°S EPR) supercritical phase separation and subseafloor mixing appear to be the main heat and mass transport mechanisms fueled by a shallow magmatic intrusion, with boron systematics ruling out major contributions from magmatic degassing processes accompanying the near-seafloor volcanism. © 2007 Elsevier Ltd. All rights reserved.